Przymusowe oszczędzanie a handel zagraniczny - Vielrose, Egon (Wydział Prawa i Administracji UAM, 1969)
In the article a measure of forced savings is derived and methods for ascertaining the presence of forced savings are given. The simplest of these methods uses data concerning the balance of external trade. It is shown that this method can be very useful and leads to valid conclusions even for developing countries with poor official statistics. The interdependence of forced savings and other economic factors and processes is analysed. It is shown that forced savings occur more often in wealthier countries than in poor ones. Moreover forced savings are in general of short duration and are influenced by changes in current government expenditure to a higher degree than by changes in investments.
Forced Savings and Foreign Trade